European Tourism Regionalization and Globalisation - Francesco Citarella (European Regional Science Association (ERSA), 2006)
The advent of the Third Millenium, as do all periods of transition, offers the starting point for proceeding towards a new interpretation of the process of development in the field of tourism which enterprise appears to lend itself as a contribution towards the achievement of certain objectives or aims of the European Union (UE), such as the protection of the environment, sustainable development, the improvement of the quality of living standards, the overcoming of conflicts for enduring peace, the growth of European regions and of employment and not least the enacting of a policy of cohesion. During recent years numerous factors such as the globalisation of the economy, the new economy, a better functioning of a single Market and the introduction of the Euro currency have all contributed to a greater internationalisation of the streams/flows and at the same time, have obliged Member states to face new challenges, which can either constitute opportunities or risks, according to the actions which will be undertaken and according to the capacity of anticipation, programming and managing of such change. On such a premise will be founded the necessity to select an integrated policy of tourism on a communitary level which, taking into consideration the specificity of the relevant sectors, will guarantee the European Community its place as representative of the most important geographical space on the world tourist market.
Keywords: 330